2020
DOI: 10.11591/ijpeds.v11.i1.pp284-290
|View full text |Cite
|
Sign up to set email alerts
|

Verifiable secure computation of linear fractional programming using certificate validation

Abstract: Outsourcing of scientic computations is attracting increasing attention since it enables the customers with limited computing resource and storage devices to outsource the sophisticated computation workloads into powerful service providers. However, it also comes up with some security and privacy concerns and challenges, such as the input and output privacy of the customers, and cheating behaviors of the cloud. Motivated by these issues, this paper focused on privacy-preserving Linear Fractional Programming (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Without proper security, a single malicious activity could compromise numerous websites. Cloud computingsecurity encompasses several challenges, including multi-tenancy, data loss [7] and leakage, ease of accessibility, identity management, unsafe APIs, inconsistencies in service level agreements, patch management, and internal threats. Enforcing security measures that provide to the diverse needs of all cloud users is challenging, as different users have varying security demands based on their objectives for using cloud services [8].…”
Section: Introductionmentioning
confidence: 99%
“…Without proper security, a single malicious activity could compromise numerous websites. Cloud computingsecurity encompasses several challenges, including multi-tenancy, data loss [7] and leakage, ease of accessibility, identity management, unsafe APIs, inconsistencies in service level agreements, patch management, and internal threats. Enforcing security measures that provide to the diverse needs of all cloud users is challenging, as different users have varying security demands based on their objectives for using cloud services [8].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the challenge of solving large-scale LFP problems, Mohammed and Lomte [23] proposed a secure and verifiable scheme to offload the computations on the cloud side. Mohammed et al [24] also focused on outsourcing of scientific computations and shown how to use certificate validation to obtain correctness guarantees for privacypreserving outsourcing of LFP problem. Adding some parameters obtained by solving a linear fractional programming problem, [25] presented an extended version of the Tikhonov regularization method.…”
Section: Introductionmentioning
confidence: 99%
“…Ghadle and Pathade [12] studied generalized hexagonal and octagonal fuzzy numbers by ranking method. Moreover, properties of the fuzzy transportation have been studied by several authors [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%